Bivalent vaccines effectively protect mice against influenza A and respiratory syncytial viruses - Sathya N. Thulasi Raman; Adrian Zetner; Anwar M. Hashem; Devina Patel; Jianguo Wu; Caroline Gravel; Jun Gao; Wanyue Zhang; Annabelle Pfeifle; Levi Tamming; Karan Parikh; Jingxin Cao; et al. (Emerging Microbes and Infections)
Influenza and Respiratory Syncytial virus (RSV) infections together contribute significantly to the burden of acute lower respiratory tract infections. Despite the disease burden, no approved RSV vaccine is available. While approved vaccines are available for influenza, seasonal vaccination is required to maintain protection. In addition to both being respiratory viruses, they follow a common seasonality, which warrants the necessity for a concerted vaccination approach. Here, we designed bivalent vaccines by utilizing highly conserved sequences, targeting both influenza A and RSV, as either a chimeric antigen or individual antigens separated by a ribosome skipping sequence. These vaccines were found to be effective in protecting the animals from challenge by either virus, with mechanisms of protection being substantially interrogated in this communication.